(untitled) (Malden, Massachusett, 2000)
This book covers classical social theory, modern social theory, and contemporary challenges to both periods. Each chapter is written by a specialist in the field, giving a clear exposition of the main concepts placed in both historical and philosophical context. Chapters contain biographical data, end of chapter lists of key concepts and a comprehensive bibliography listing the primary and secondary literature relevant to the material
Keywords: Xã hội học,Sociology; Lý thuyết,Philosophy